2018
DOI: 10.3389/fpls.2018.01280
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Major QTLs Associated With First Pod Height and Candidate Gene Mining in Soybean

Abstract: First pod height (FPH) is a quantitative trait in soybean [Glycine max (L.) Merr.] that affects mechanized harvesting. A compatible combination of the FPH and the mechanized harvester is required to ensure that the soybean is efficiently harvested. In this study, 147 recombinant inbred lines, which were derived from a cross between ‘Dongnong594’ and ‘Charleston’ over 8 years, were used to identify the major quantitative trait loci (QTLs) associated with FPH. Using a composite interval mapping method with WinQT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…The experimental RIL population used in this study (‘Charleston’ × ‘Dongnong594′, n = 150) originated from two individual lines, Charleston and Dongnong594 [ 81 ]. To map QTLs controlling nodule-related traits in the RIL population of ‘Charleston’ × ‘Dongnong594′, we used the method of composite interval mapping [ 61 ], with WinQTL Cartographer [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…The experimental RIL population used in this study (‘Charleston’ × ‘Dongnong594′, n = 150) originated from two individual lines, Charleston and Dongnong594 [ 81 ]. To map QTLs controlling nodule-related traits in the RIL population of ‘Charleston’ × ‘Dongnong594′, we used the method of composite interval mapping [ 61 ], with WinQTL Cartographer [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…The experimental RIL population used in this study (n = 150) was derived from the cross of Charleston and Dongnong594 (Jiang et al, 2018). A high-density genetic map with 5,308 specific locus amplified fragment sequencing (SLAF-seq) markers had been constructed via this population (Qi et al, 2014).…”
Section: The Conditional Quantitative Trait Locus Mapping Of Nodulation-related Traitsmentioning
confidence: 99%
“…To introduce the resistance against Micosphaera diffusa Cooke & Peck, which causes powdery mildew disease (PMD), to Chinese soybean cultivars, researchers have made use of the PMD-resistant soybean cultivar BRSMG68 (B13) from Brazil (Jiang et al 2018). The PMD resistance locus was mapped to a 188-kb region on chromosome 16 of B13 that contains 17 disease resistance genes accounting for 78% of the phenotypic differences within the mapping population (Jiang et al 2018).…”
Section: Progress On Soybean Molecular Breeding In Chinamentioning
confidence: 99%
“…Pod distribution on the soybean plant also affects the harvest index and is influenced by a number of minor-effect loci. Using 7-year worth of data, a study identified 11 major QTLs and 90 epistatic pairs controlling the first pod height (Jiang et al 2018). Another study identified 47 QTLs associated with the distribution of pods with different numbers of seeds at the upper, middle, and lower sections of the soybean plant (Ning et al 2018).…”
Section: Progress On Soybean Molecular Breeding In Chinamentioning
confidence: 99%